Silver nanoparticles as potential antibiofilm agents against candida albicans, candida tropicalis and candida glabrata - Galera, Ivana Laura Delia (2021)
Adhesion of different organisms to surfaces leading to biofilm formation can cause a number of problems in areas as diverse as health, food industry and the shipping industry. Submerged structures are quickly colonized by a succession of organisms in a process denominated biofouling that is of particular interest to the shipping industry, as it involves an important economic burden. Biofouling is a stepwise process that starts with the absorption of organic matter followed by the adhesion of different microorganisms, such as bacteria, that form a biofilm. This in turn facilitates the attachment and growth of other organisms, such as algae and barnacles. Among the different strategies used to prevent biofouling, the use of biocides has been banned in the last decade due to environmental concerns, and antibiofouling surface coatings appeared as an environmentally friendly alternative. Polydimethylsiloxane (PDMS) is a silicone coating with antifouling properties which may be modified to increase its roughness, as the presence of nanoscale roughness has been shown to decrease biofilm formation. Multi Walled Carbon Nanotubes (MWCNT) or exposure to Br2 vapors with or without UV irradiation that produce depressions of different sizes.